ChemInform Abstract: A General Intramolecular Friedel—Crafts Approach to Functionalized Pyrrolo[3, 2, 1‐ij]quinolin‐4‐ones. Issue 7 (22nd February 2013) - Patil, Dadasaheb V.; Cavitt, Marchello A.; Grzybowski, Paul; France, Stefan
Abstract The synthesis of title compounds (II) and (IV) via intramolecular Friedel‐Crafts alkylation of precursors (I) and (III) is described.